Gender differences in the provision of injection initiation assistance: a comparison of three North American settings - Stephanie A. Meyers; Ayden Scheim; Sonia Jain; Xiaoying Sun; M. J. Milloy; Kora DeBeck; Kanna Hayashi; Richard S. Garfein; Dan Werb (BMC, 2018)
Abstract Aim Individuals experience differential risks in their initiation into drug injecting based on their gender. Data suggest women are more likely to be injected after their initiator and to share injection equipment. Little is known, however, regarding how gender influences the risk that people who inject drugs (PWID) may assist others into injection initiation. We therefore sought to investigate the role of "initiator" gender in the provision of injection initiation assistance across multiple settings. Methods We employed data from PReventing Injecting by Modifying Existing Responses (PRIMER), a multi-cohort study investigating factors influencing injection initiation assistance provision. Data were drawn from three cohort studies of PWID in San Diego, USA (STAHR II); Tijuana, Mexico (El Cuete IV); and Vancouver, Canada (VDUS). Site-specific logistic regression models were fit, with lifetime provision of injection initiation assistance as the outcome and gender as the independent variable. Results Overall, 3.2% (24/746) of the women and 4.6% (63/1367) of the men reported providing injection initiation assistance. In Tijuana, men were more than twice as likely to have provided injection initiation assistance after controlling for potential confounders (adjusted odds ratio = 2.17, 95% confidence interval: 1.22-3.84). Gender was not significantly associated with providing injection initiation assistance in other sites. Conclusion We identified that being male in Tijuana, specifically, was associated with providing injection initiation assistance, which could inform targeted outreach aimed at reducing the influence of PWID populations on non-injectors in this site. This will likely require that existing interventions address gender- and site-specific factors for effectiveness.